Effect of Time Variation on Chlorophyll Concentration in Cocoa Leaf Extraction using the UAE (Ultrasonic Assisted Extraction) Method - Rahmawati, Istiqomah; Shabrina, Nadhilah; Fachri, Boy Arief; Amini, Helda Wika; Palupi, Bekti; Rizkiana, Meta Fitri; Nurtsulutsiyah, Nurtsulutsiyah; Pradipta, Shima Nuril; Afwal, Diza Raudhatul; Reza, Muhammad (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
Until now, Cocoa (Theobroma cacao L.) plantation is a sector that has been continuously cultivated. Cocoa leaves contain chlorophyll, which is an important pigment in photosynthesis as sunlight absorber. The aim of this study is to determine the effect of extraction time to the concentration of chlorophyll in cocoa leaves. The extraction time was varied from 5 to 25 min with constant variables, namely power and ratio of raw materials. In this study, Ultrasonic Assisted Extraction (UAE) method was used due to its effectiveness. The concentration of obtained chlorophyll was determined by using UV-Vis spectrophotometry. The optimum extraction time was 15 min producing concentration of chlorophyll a of 9.39 mg/L, chlorophyll b of 4.78 mg/L, and total chlorophyll of 14.16 mg/L.